2011
DOI: 10.1002/hep.24423
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of fecal microbial communities in patients with liver cirrhosis

Abstract: Liver cirrhosis is the pathologic end stage of chronic liver disease. Increasing evidence suggests that gut flora is implicated in the pathogenesis of liver cirrhosis complications. The aim of this study was to characterize the fecal microbial communities in patients with liver cirrhosis in comparison with healthy individuals. We recruited 36 patients with liver cirrhosis and 24 healthy controls. The fecal microbial community was analyzed by way of 454 pyrosequencing of the 16S ribosomal RNA V3 region followed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

56
797
6
9

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 888 publications
(896 citation statements)
references
References 47 publications
56
797
6
9
Order By: Relevance
“…Cirrhosis patients have colonic microbiota that are different from that of healthy control subjects. 10,11 Increases in Enterobacteriaceae and Enterococcus with a reduction in Bifidobacterium species were noted in one report. Whether these changes are a cause or a consequence of cirrhosis is not clear.…”
Section: Microbiota and Liver Diseasementioning
confidence: 88%
See 1 more Smart Citation
“…Cirrhosis patients have colonic microbiota that are different from that of healthy control subjects. 10,11 Increases in Enterobacteriaceae and Enterococcus with a reduction in Bifidobacterium species were noted in one report. Whether these changes are a cause or a consequence of cirrhosis is not clear.…”
Section: Microbiota and Liver Diseasementioning
confidence: 88%
“…10 An earlier report had indicated a reduced proportion of bacteroidetes and an increase in proteobacteria and fusobacteria. 11 In fact, a positive correlation was observed between Child-Turcotte-Pugh score and streptococcaceae. 11 Another report contradicted these findings vis-à-vis the diversity in intestinal microbiota amongst subjects with hepatitis B virus-related cirrhosis, subjects with chronic hepatitis B, and controls.…”
Section: Microbiota and Liver Diseasementioning
confidence: 98%
“…There is a reduction in Veillonellaceae (gram negative cocci) and an increase in Eubacteriaceae (gram positive cocci). 40,41 Rifaximin is effective and well tolerated, with minimal systemic absorption. A meta-analysis comparing rifaximin with lactulose found that patients taking rifaximin fared better than those on lactulose.…”
Section: Correct Answers: C and Ementioning
confidence: 99%
“…Veillonellaceae are gram negative cocci that are more abundant in the stool of patients with cirrhosis compared to healthy individuals. 16 The initial studies for rifaximin demonstrated its efficacy in the management of OHE. Compared to lactulose, rifaximin is more effective in the treatment of OHE.…”
Section: Rifaximinmentioning
confidence: 99%
“…The gut microbiota plays an integral role in the production of ammonia and other toxins resulting in oxidative stress/inflammation. [16][17][18][19] It would only seem natural that treatment modalities in CHE would focus on the modulation of the gut flora. Therapeutic strategies for CHE must be extrapolated from MHE trials as CHE is a relatively recent term and no studies on therapy are available at this time.…”
mentioning
confidence: 99%